Perbedaan Orientasi Keberagamaan Pada Siswa Santri Pondok Pesantren Tradisional dan Siswa Sekolah Islam Swasta - Achmad, Anisyah Yasmin, Drs. Soleh Amini Yahman, M.Si, Psi (2016)
This study aims to understand and describe the religious orientation of which is owned by a traditional boarding school students and students of private Islamic schools. This research was conducted in two places, namely SMA Muhammadiyah 2 Surakarta and Traditional Pondok Pesantren Al-Mu'min Sragen. Research subjects in this study of 100 people with 50 high school students Muhammadiyah 2 Surakarta and 50 boarding school students of Al-Mu'min Sragen. Sampling was conducted by random sampling technique. The method used in this penlitian is a quantitative method by using religious orientation scale. This research data analysis techniques using independent sample t-tests. Based on the results of independent testing of samples t-test t-test values obtained at t = -0.399 with coefficient sig = 0.217 (p> 0.005) which means there is no difference in the orientation of traditional religious boarding school students and students of private Islamic schools. Subjects in this study had a religious orientation is high.